2022
DOI: 10.17515/resm2022.371ma1207
|View full text |Cite
|
Sign up to set email alerts
|

The freeze-thaw durability of concrete containing the rubber aggregate of tire waste

Abstract: The influence of rubber aggregate of tire waste (RATW) under cyclic freezethaw attack of concrete was studied. Various concrete mixes were prepared: a plain concrete (PC) produced with natural sand and rubber concretes (CRATW) included the RATW ratios of 5, 10, and 15 % such as a partial replacement with the natural sand aggregate (NSA). After the samples exposed to the different freeze-thaw cycles (120, 240, 340), their following properties were evaluated: visual observations, mass loss, dynamic modulus of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, the hydrophobic nature of polymer waste can inhibit the hydration reaction of cement by limiting the movement (access) of water in the concrete mix. A negative effect on the concrete’s compressive strength parameter was also observed after adding other polymeric materials, such as PET [ 11 , 12 , 14 , 15 , 16 ], EPE [ 18 ], EPS [ 19 , 20 , 21 , 22 ], and rubber [ 41 , 43 , 45 , 46 , 47 ]. However, some authors report that the addition of PET [ 10 , 13 ], EPS [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], or PP [ 32 , 34 , 38 ] wastes increases the compressive strength of concretes modified with this waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the hydrophobic nature of polymer waste can inhibit the hydration reaction of cement by limiting the movement (access) of water in the concrete mix. A negative effect on the concrete’s compressive strength parameter was also observed after adding other polymeric materials, such as PET [ 11 , 12 , 14 , 15 , 16 ], EPE [ 18 ], EPS [ 19 , 20 , 21 , 22 ], and rubber [ 41 , 43 , 45 , 46 , 47 ]. However, some authors report that the addition of PET [ 10 , 13 ], EPS [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], or PP [ 32 , 34 , 38 ] wastes increases the compressive strength of concretes modified with this waste.…”
Section: Resultsmentioning
confidence: 99%
“…There are also several literature reports on the use of rubber in the production of concrete [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Concretes with the addition of rubber recyclate are usually characterized by lower values of mechanical parameters than concretes produced without the addition of waste [ 41 , 43 , 45 , 46 , 47 ], although there are also reports [ 40 ] that the addition of this material does not affect the mechanical properties of concrete. The decrease in the compressive strength after adding waste rubber, as shown in the works, is mainly related to the size of the introduced waste material.…”
Section: Introductionmentioning
confidence: 99%
“…This waste pollutes the natural sources of air, groundwater, and soil, because it contains polluted and toxic elements such as heavy metals [1][2][3]. Reliable environmental references recommended reusing them with building materials as a concrete aggregate [2][3][4][5]. However, many studies have shown that the inclusion of rubber particles with concrete composite produced a high reduction in their mechanical performance [6,7].…”
Section: Introductionmentioning
confidence: 99%